The Role of Copper Salts and O2 in the Mechanism of C≡N Bond Activation for Facilitating Nitrogen Transfer Reactions. Issue 13 (7th February 2022) - Ghosh, Boyli; Banerjee, Ambar; Roy, Lisa; Manna, Rabindra Nath; Nath, Rounak; Paul, Ankan
Abstract: C≡N bond scission can be a potential avenue for the functionalization of chemical bonds. We have conducted a computational study, using density functional theory (DFT) and ab initio multireference CASSCF methods, to unravel the intricate mechanistic pathways traversed in the copper‐promoted, dioxygen‐assisted reaction for the formation of aryl isocyanate species from aryl aldehyde. This aryl isocyanate species acts as an active species for C≡N bond cleavage of coordinated cyanide anion enabling nitrogen transfer to various aldehydes. Electronic structure analysis revealed that under all the reaction conditions radical‐based pathways are operative, which is in agreement with the experimental findings. The major driving force is a Cu II/I redox cycle initiated by single‐electron transfer from the carbon center of the nitrile moiety. Our study reveals that the copper salts act as the "electron pool" in this unique nitrogen transfer reaction forming an aryl isocyanate species from aryl aldehydes. Abstract : A detailed theoretical study on the intricate mechanism and electron transfer landscape of oxygen‐assisted copper‐promoted formation of aryl nitrile species starting from aryl aldehyde. In this reaction the major driving force is the redox cycle of the copper center (Cu II /Cu I ), which acts as the electron source and sink whenever necessary along the course of reaction.